2014
DOI: 10.1158/0008-5472.can-13-3583
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Expression of Adenosine A2A Receptor Suppresses T and NK Cell Responses in the Solid Tumor Microenvironment

Abstract: High concentrations of adenosine in tumor microenvironments inhibit anti-tumor cytotoxic lymphocyte responses. Although T cells express inhibitory adenosine A2A receptors (A2ARs) that suppress their activation and inhibit immune killing of tumors, a role for myeloid-cell A2ARs in suppressing the immune response to tumors has yet to be investigated. In this study we show that the growth of transplanted syngeneic B16F10 melanoma or Lewis lung carcinoma cells is slowed in Adora2af/f–LysMCre+/− mice, which selecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
216
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(223 citation statements)
references
References 39 publications
6
216
0
1
Order By: Relevance
“…Extracellular nucleotides also regulate the fate of immune cells, 14,35 and immunosuppressive properties of adenosine in solid carcinomas have been extensively described. 20 Moreover, hypoxia modulates immune cell sensitivity to adenosine via increase of HIF1a expression which leads to modulation of CD73 and ADORA2A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracellular nucleotides also regulate the fate of immune cells, 14,35 and immunosuppressive properties of adenosine in solid carcinomas have been extensively described. 20 Moreover, hypoxia modulates immune cell sensitivity to adenosine via increase of HIF1a expression which leads to modulation of CD73 and ADORA2A.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Ohta, Sitkovsky and others showed that, among the different adenosine receptors (A1, A2A, A2B and A3), 26 the adenosine receptor 2A has a major role in the attenuation of inflammation and tissue damage. 20,21,[32][33][34][35] These studies evidenced the CD39-CD73-adenosine receptor axis blockade as a promising therapeutic target. 31,[36][37][38][39][40][41][42] In line with these studies and with the objective to better understand the mechanism involved in the acquisition by TAM of an immunoregulatory phenotype, this study aimed at evaluating the impact of ATP and ATP metabolites on TAM functions.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] In contrast to these suppressive cytokines, several cytokines such as IL-2, IL-12, IL-15, IL-18, and IL-21 are known to activate NK cells both in vitro and in vivo, and are proposed to increase the therapeutic potential of these cells for adoptive therapy. 13 Due to their natural cytotoxic property in the peripheral blood, 14 the use of NK cells has been identified as one of the promising adoptive cellular immunotherapies to control cancer.…”
Section: Cd11bmentioning
confidence: 99%
“…6,7 In contrast, peripheral regulatory T cells (pTreg) or myeloid-derived suppressor cells (MDSC) are activated by ADO signaling via A 2A R and their immunosuppressive functions are enhanced. 8,9 The role of A 1 R or A 3 R in ADO-mediated immune regulation is not entirely clear, although 5 0 -AMP was reported to be an A 1 R agonist with affinity equal to or better than that of ADO. 10 In cancer, ADO is viewed as a pro-tumor factor which suppresses antitumor functions of Teff and promotes functions of suppressor cells (Treg and MDSC).…”
Section: Introductionmentioning
confidence: 99%